KODANGAL FARMER SERVICE PRODUCER COMPANYA CONSTRAINT ANALYSIS - and G. SAMUEL, D. A. RAJINI DEVI, R. VIJAYA KUMARI T. LAVANYA, D. SRINIVASA CHARY (The Journal of Research, PJTSAU, 2021)
Farmer Producer Organisations is a crucial strategy for creating an ecosystem for enhancing farmers profits. Ex-post facto research design was adopted to examine the constraints faced by different stake holders involved in formation and operationalisation of Kodangal Farmer service Producer Company (KFPC) in Telangana state. Data was collected from 30 memberfarmers, 30 non-member farmers, 10 Board of Directors (BoDs) and 12 officials of the FPC. Hence, total samples becomes 82. Garrett tanking technique of constraint analysis showed that lack of awareness among farmers and socio-cultural barriers were the major problems faced by the supporting institution and Board of Directors (BoDs) at the time of formation of FPC. During operationalisation, lack of adequate number of godowns, store houses, illiteracy, weak educational exposure in maintainingaccounts and records were the major hindering factors for supporting institution and BoDs respectively. Irregular procurement of produce was the major operational constraint opined by the member farmers. High cost of labour and lack of assured procurement facilities were the major labour and economic and marketing constraints respectively.